Sitagliptin induced acute severe nasopharyngitis - Krishnan, V.; Rai, Shivali (International Journal of Basic & Clinical Pharmacology, 2017)
Acute nasopharyngitis is one of the distressing adverse effects seen with the use of dipeptidyl peptidase-4 inhibitors like sitagliptin. Here, we report a case of acute severe nasophryngitis with the use of sitagliptin for diabetes mellitus.